EFFICACY AND SAFETY OF REGDANVIMAB THERAPY IN MODERATE COURSE OF COVID-19 - Ликстанов, Михаил Исаакович; Кушнир, Ирина Николаевна; Ромасюк, Анна Владимировна; Хмелева, Ирина Анатольевна; Власова, Екатерина Александровна; Маталасова, Мария Сергеевна; Шофорусь, Татьяна Владимировна; Якушенко, Мария Геннадьевна; Стрельцова, Елена Владимировна; Аскандеров, Павел Аскандерович; Мозес, Вадим Гельевич; Рисовер, Евгения Юрьевна; et al. (Medicine in Kuzbass, 2023)
The efficacy and safety of therapy with a human monoclonal antibody (international patent name Regdanvimab) in patients with a moderate course of COVID-19 was evaluated. A total of 41 patients (48.8 % women and 51.2 % men) were treated during the period of mixed distribution of delta and omicron strains of SARS-CoV-2. Regdanvimab was administered in a hospital setting based on the calculation of the amount of 40 mg/kg per patient's body weight. The median dose of regdanvimab was 3200 (2720; 4000) mg, the minimum dose was 2040 mg, and the maximum dose was 4800 mg.When prescribing regdanvimab, on the second day there was an improvement in the clinical picture and laboratory parameters characterizing the course of the infectious process. The lethality of patients during the study was due to the severity of the course of concomitant diseases and emphasizes the need for an integrated approach to the management of comorbid patients with the involvement of specialists from related fields, such as nephrologists, oncologists, chemotherapists, cardiologists, etc., in prescribing therapy.Thus, Regdanvimab proved the efficacy and safety of use in patients with COVID-19 during routine practice, while the clinical efficacy of the drug was shown in a mixed cohort of delta-omicron strains.
Keywords: COVID-19; Regdanvimab; treatment